Characterising violent deaths of undetermined intent: a population-based study, 1999–2012. Issue 6 (6th October 2017) - Lachaud, James; Donnelly, Peter; Henry, David; Kornas, Kathy; Fitzpatrick, Tiffany; Calzavara, Andrew; Bornbaum, Catherine; Rosella, Laura
Abstract : Objectives: Violent deaths classified as undetermined intent (UD) are sometimes included in suicide counts. This study investigated age and sex differences, along with socioeconomic gradients in UD and suicide deaths in the province of Ontario between 1999 and 2012. Methods: We used data from the Institute for Clinical Evaluative Sciences, which has linked vital statistics from the Office of the Registrar General Deaths register with Census data between 1999 and 2012. Socioeconomic status was operationalised through the four dimensions of the Ontario Marginalization Index. We computed age-specific and annual age-standardised mortality rates, and risk ratios to calculate risk gradients according to each of the four dimensions of marginalization. Results: Rates of UD-classified deaths were highest for men aged 45–64 years residing in the most materially deprived (7.9 per 100 000 population (95% CI 6.8 to 9.0)) and residentially unstable (8.1 (95% CI 7.1 to 9.1)) neighbourhoods. Similarly, suicide rates were highest among these same groups of men aged 45–64 living in the most materially deprived (28.2 (95% CI 26.1 to 30.3)) and residentially unstable (30.7 (95% CI 28.7 to 32.6)) neighbourhoods. Relative to methods of death, poisoning was the most frequently used method in UD cases (64%), while it represented the second most common method (27%) among suicides after hanging (40%). Discussion: The similarities observed between both causes of death suggest that at least a proportion of UD deaths may be misclassified suicide cases. However, the discrepancies identified in this analysis seem to indicate that not all UD deaths are misclassified suicides.